2004
DOI: 10.1111/j.1467-839x.2004.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternalistic leadership and subordinate responses: Establishing a leadership model in Chinese organizations

Abstract: Paternalistic leadership (PL) is the prevalent leadership style in Chinese business organizations. With an approach similar to patriarchy, PL entails an evident and powerful authority that shows consideration for subordinates with moral leadership. Although PL is widespread in Chinese business organizations, very few studies have focused on this leadership style and those that have were simply conceptual analyses and not empirical studies. We sampled 543 subordinates from local businesses in Taiwan to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
1,019
9
29

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(1,090 citation statements)
references
References 20 publications
33
1,019
9
29
Order By: Relevance
“…The scale was taken from Cheng et al (2004). Paternalistic leadership has three distinct dimensions named authoritarian leadership, benevolent leadership and moral leadership.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale was taken from Cheng et al (2004). Paternalistic leadership has three distinct dimensions named authoritarian leadership, benevolent leadership and moral leadership.…”
Section: Methodsmentioning
confidence: 99%
“…Benevolence means that the leader's behavior demonstrates individualized, holistic concern for subordinates' personal or familial well being. Moral leadership can be broadly depicted as a leader's behavior that demonstrates superior personal virtues, self-discipline, and unselfishness (Cheng et al, 2004).…”
mentioning
confidence: 99%
“…Research on indigenous Chinese leadership behavior shows that a paternalistic leadership style that focuses on authoritarianism, benevolence, and moral leadership is prevalent in Chinese societies (Cheng, Chou, & Farh, 2000;. Interestingly, although most studies have found that authoritarianism has a negative effect on the attitudinal and behavioral outcomes of subordinates (Cheng, Shieh, & Chou, 2002;Farh, Cheng, Chou, & Chu, 2004), a number of studies have found that authoritarianism has positive effects on employee loyalty to supervisors, commitment to organization, subordinate identification, compliance, and gratitude (Cheng, Chou, Huang, Farh, & Peng, 2003;Cheng, Chou, Huang, Wu, & Farh, 2004).…”
Section: Potential Deviations Of Conflict Management Styles In the Chmentioning
confidence: 99%
“…based on EDI, is a challenging task that must not only take account of differences between innovation strategies, but also of human and endowment factors differing between cultures, organisations, and institutions. Apart from paternalistic leadership research (Cheng et al, 2004), research on indigenous Chinese management theories (inside-out) has been scarce so far. Up to now, scholars have been mainly occupied with transplanting 'Western' management thoughts and assessing their applicability in China, flavouring them with 'Chinese characteristics' (Zhang et al, 2012).…”
Section: Limitations and Implications For Further Researchmentioning
confidence: 99%
“…On the one hand, it has been noticed many times that China has rather little participatory tradition, but one of strong leadership and clear power structures (Chen and Aryee, 2007;Huo and Von Glinow, 1995). Organisational practice is dominated by forms of directive (Sagie, Zaidman, Amichai-Hamburger, Te'eni, and Schwartz, 2002) and paternalistic leadership (Cheng, Chou, Huang, Wu, and Farh, 2004), and leaders put less emphasis on employee participation, particularly with regard to innovations -as it seems. Accordingly, there is almost no research on EDI or other forms of employee participation in the organisational context in China.…”
Section: Introductionmentioning
confidence: 99%